Peningkatan Kualitas Pembelajaran IPA Melalui Starartegi SETS - Nuryani Harefa (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The writing of this thesis stems from the failure of the teacher in implementing science learning. Teachers have not been optimal in learning science. This has an impact on the low quality of science learning and the low learning outcomes of Grade IVa students. Of the 24 students, only 4 students have finished studying and 20 other students have not finished studying. The level of student learning completeness is 20%. To solve this problem, the SETS strategy is used. The formulation of the problem in the research The results showed that the students' learning outcomes in the first cycle were an average class of 64.8, with 9 students having completed their studies, 16 students had not completed, and the level of student learning completeness was 36%. These results increased in the second cycle of learning with an average grade of 73.0, the number of students completing learning 17 students, not completing 8 students with a level of student learning completeness of 68%. The results of observations on the ability of teachers to manage learning cycle I an average of 2.2 with sufficient qualifications (C) cycle II increased to an average of 3.5 with good qualifications (B). The results of observations on student learning activities showed that the average cycle I was 1.6 with the category Enough (C) and cycle II an average of 3.2 with the category Good (B). Keywords: environment; SETS  Abstrak: Penulisan  skripsi  ini bermula  dari  kegagalan  guru  dalam  melaksanakan pembelajaran   IPA.  Guru  belum  optimal  dalam  pembelajaran   IPA.  Hal  ini berdampak  pada  rendahnya  kualitas  pembelajaran  IPA  dan  rendahnya  hasil belajar IPA siswa Kelas IVa. Dari 24 siswa hanya 4 siswa yang tuntas belajar dan 20 siswa lainnya belum tuntas belajar. Tingkat ketuntasan  belajar siswa 20%. Untuk mengatasi masalah tersebut digunakan Strategi SETS. Rumusan masalah dalam penelitian Hasil penelitian  menunjukkan  hasil belajar siswa pada siklus I rata-rata kelas 64,8, dengan jumlah siswa tuntas belajar 9 siswa, belum tuntas 16 siswa, tingkat  ketuntasan  belajar siswa 36%. Hasil ini meningkat  pada pembelajaran siklus II dengan nilai rata-rata kelas 73,0, jumlah siswa tuntas belajar 17 siswa, belum tuntas 8 siswa dengan tingkat ketuntasan belajar siswa 68%. Hasil pengamatan terhadap kemampuan guru mengelola pembelajaran siklus I rata-rata 2,2 dengan kualifikasi cukup (C) siklus II naik menjadi rata-rata 3,5 dengan kualifikasi  Baik  (B).  Hasilpengamatan  terhadap  aktifitas  belajar  siswa menunjukkan siklus I rata-rata 1,6 dengan ketegori Cukup (C) dan siklus II rata- rata 3,2 dengan kategori Baik (B). Kata  kunci: lingkungan; SETS